Where Do Betas Come From? Asset Price Dynamics and the Sources of Systematic Risk - Campbell, John Y.; Mei, Jianping (Review of Financial Studies, 1993)
In this article we break assets’ betas with common factors into components attributable to news about future cash flows, real interest rates, and excess returns. To achieve this decomposition, we use a vector autoregressive time-series model and an approximate log-linear present value relation. The betas of industry and size portfolios with the market are largely attributed to changing expected returns. Betas with inflation and industrial production reflect opposing cash flow and expected return effects. We also show how asset pricing theory restricts the expected excess return components of betas.